2017
DOI: 10.1177/0897190017747083
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Pharmacist-Driven Aldosterone Antagonist Stewardship Program in Patients With Heart Failure

Abstract: In patients with HFrEF, a pharmacist-driven aldosterone antagonist optimization initiative significantly increased appropriate prescribing and documentation for aldosterone antagonist therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…28 Using our prescriber-alert tool, we observed similar improvements to β-blockers and overall GDMT prescription, as seen in inpatient and outpatient settings using alternative interventions, 27,28 while also observing improvement to MRA prescription that was reported for hospital inpatients. 26,27 Our tool was patient-specific and provided the prescriber an opportunity to consult pharmacy, making the alert more targeted, a strategy that previous HFrEF stewardship programs were also able to successfully use. [26][27][28] In contrast to more resource-intensive initiatives, this stewardship tool can easily be implemented by non-pharmacist health care providers, does not require electronic patient charts to execute and was not found to be time-consuming to implement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…28 Using our prescriber-alert tool, we observed similar improvements to β-blockers and overall GDMT prescription, as seen in inpatient and outpatient settings using alternative interventions, 27,28 while also observing improvement to MRA prescription that was reported for hospital inpatients. 26,27 Our tool was patient-specific and provided the prescriber an opportunity to consult pharmacy, making the alert more targeted, a strategy that previous HFrEF stewardship programs were also able to successfully use. [26][27][28] In contrast to more resource-intensive initiatives, this stewardship tool can easily be implemented by non-pharmacist health care providers, does not require electronic patient charts to execute and was not found to be time-consuming to implement.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions for the improvement and optimization of GDMT prescription in patients with HFrEF have shown success in elevating both individual and combined therapy prescription upon hospital discharge 26,27 or at 30-day follow-up for outpatients. 28 Using our prescriber-alert tool, we observed similar improvements to β-blockers and overall GDMT prescription, as seen in inpatient and outpatient settings using alternative interventions, 27,28 while also observing improvement to MRA prescription that was reported for hospital inpatients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence suggests pharmacist-led medication optimization in HF has improved medication adherence and guidelinedirected medical therapy (GDMT) as well as decreased hospitalization rates for HF. [3][4][5][6][7][8] In addition to improvements in clinical outcomes, a recent prospective observational study has demonstrated an annual total savings of $830,748 ($149,566 from clinical interventions and $681,182 from patient direct out-of-pocket expense reduction) with the addition of a cardiology clinical pharmacy specialist in a preventive cardiology practice. 9 Thus, pharmacists are integral to optimizing population health through better patient management and allocation of resources.…”
Section: Introductionmentioning
confidence: 99%